A Case of Crossed Left Renal Ectopia Identified during Colostomy Reversal. (18th January 2017) - NeMoyer, Rachel; Narayanan, Sumana; Maloney-Patel, Nell
Abstract : Unilateral crossed renal ectopia without fusion is an uncommon anatomic anomaly, which often goes undiagnosed. We report a case of this renal variant discovered incidentally during colostomy reversal after Hartmann's procedure for diverticular stricture.